Habituating The Heart: The Role of Early Volunteerism in Developing Psychological Traits of Christian Leadership - Tan Lie Lie; Janto Chandra; Warren Chandra (Journal of Educational, Health and Community Psychology, 2026)
This study examined the psychological mechanisms through which early volunteerism among young Christians contributes to the formation of leadership traits. A growing body of literature underscores the importance of formative experiences in shaping prosocial behavior and leadership character; however, research linking habitual early volunteerism specifically to Christian leadership psychology remains limited. Using a quantitative correlational design, 214 young Christian volunteers (ages 17–25) from Protestant churches in Jakarta and Salatiga were surveyed using the Volunteer Motivation Inventory (VMI), the Leadership Trait Questionnaire (LTQ), and the Christian Leadership Identity Scale (CLIS). Results indicated significant positive correlations between habitual volunteerism and traits of empathy (r = .58, p < .01), self-regulation (r = .51, p < .01), and servant leadership orientation (r = .63, p < .01). Habit strength moderated the relationship between motivation and leadership trait development. These findings suggest that structured, early-stage voluntary service functions as a psycho-spiritual incubator for leadership development within Christian communities.